Impact of Social Media on Knowledge, Attitude, and Performance of the Post-discharge COVID-19 Patients: An Educational Intervention - Mitra Zolfaghari; Maryam Etemadi; Manijeh Hooshmandja (Interdisciplinary Journal of Virtual Learning in Medical Sciences)
Background: Considering the significance of adherence to treatment in patients with COVID-19 and the role and benefits of education through social media, this study aimed to investigate the impact of social media-based intervention on improving the knowledge, attitude, and performance of patients with COVID-19 following their hospital discharge.Methods: This interventional study was carried out from November 2021 to July 2022 at a hospital in Tehran, Iran, involving patients diagnosed with COVID-19. The participants were categorized into two groups: an intervention group that received social media-based training and a control group that underwent conventional training. A total of 60 eligible patients were selected through convenience sampling and randomly assigned to either the intervention group (n=30) or the control group (n=30). The participants' knowledge, attitudes, and performance were assessed using a questionnaire developed by the researchers, both prior to and two weeks after the educational intervention. Data analysis was performed using SPSS version 24, employing independent and paired T-tests as well as Analysis of Covariance (ANCOVA) for statistical evaluation.Results: A comparison of pre-test and post-test variables between the two groups demonstrated a significant difference in the intervention group (P=0.001). Furthermore, the analysis of between-group differences indicated that the intervention led to a substantial enhancement in post-test scores regarding attitude, knowledge, and performance in the intervention group when compared to the control group (P<0.001).Conclusion: The study's findings indicate that interventions delivered via social media significantly improve the knowledge, attitudes, and behaviors of patients with COVID-19 after their hospital discharge. These results underscore the critical role of social media in enhancing patients' awareness and skills in health management.